Implantação de políticas públicas de ações afirmativas no contexto da UFAL: estudo de caso de 2005 a 2006 - Santos, Marizângela Melo dos (2014)
Education changes through time according to the socioeconomic and political context in relation to the society in which it therefore applies variable. The concept of education is a goal to achieve and Brazil has been making major investments in the area to raise their level of basic and higher education, however, still insufficient to show a real increase in international education development index. With so many differences Brazil has been investing in public policies, as a means of providing to reduce inequality, whether social, racial and gender order, giving the needy a new perspective on life. The public policy of affirmative action for admission to higher education are fair and necessary, represent part of the government's investment and at the same time raise a big difference in the quality and lack of elementary and secondary education of needy social layer in relation to the wealthy. Thus this dissertation shows how the implementation of quotas in the Federal University occurred, analyzing how this deployment is providing access to the upper level. Evidently the quota system is positive about many aspects both for the institution, and for the teachers and students.